First record of Crepidobothrium gerrardii (Cestoda: Proteocephalidae) in Peru - Gomez-Puerta, Luis A. (2011)
It is the first record of cestode Crepidobothrium gerrardii in Peru, parasitizing the intestine of a boa constrictor (Boa constrictor) from Loreto. Four tapeworms were studied and identified as C. gerrardii.